Martha's guests. Master chefs [videorecording (DVD)]. - Stewart, Martha; Batali, Mario; Flay, Bobby; Bastianich, Lidia (Warner Home Video, 2006)
Join Martha in her kitchen as she and some of her favorite culinary experts team up to make a variety of mouth-watering dishes. Features spectacular dishes including Spaghetti alla Carbonara, Pad Thai, Coq au Vin, Olive-stuffed Flank Steak, Chiles Anchos Rellenos.